ANALISIS EFEKTIVITAS TERMINAL ADIWERNA DI KABUPATEN TEGAL - Dimas Anugrah Dwi Saputra; Rezza Pamalis (Departemen Administrasi Publik, Universitas Diponegoro, 2018)
The Adiwerna Terminal is a type C terminal located in Tegal Regency which serves passengers and city and rural transportation. In its management, the Adiwerna terminal has not gone well. Problems were found such as the absence of urban and rural transportation entering the terminal, terminal facilities that were not maintained, limited human resources, and services that were not optimal. This makes the writer interested in conducting research on the effectiveness of the Adiwerna terminal in Tegal Regency. This study used a qualitative descriptive study with the location of the research in the Adiwerna terminal. Data collected from interviews, records, until data from print and electronic media were collected into one to draw conclusions that more sharply illustrate the results of observations. As a result, the effectiveness of the Adiwerna terminal in Tegal Regency has not been optimal. In terms of time and cost it is not yet efficient. Service procedures are only regulated with 1 (one) regulation and do not have SOPs. Coordination between superiors and subordinates went well but still did not show high employee responsiveness. The availability of infrastructure is adequate but not well maintained so that passengers cannot use the facilities to the full. Things that are driving factors for the effectiveness of the Adiwerna terminal are 1) Planning Activities, 2) Organizing, 3) Control, 4) Direction, and 5) Decision Making. While the inhibiting factors of effectiveness found in the Adiwerna terminal are 1) Placement, 2) Motivation, and 3) Communication.